MANIFESTATION OF RESPIRATORY FUNCTIONS OF HOCKEY PLAYERS UNDER TRAINING IMPACTS OF DIFFERENT DIRECTIONS - Mikhailov, K.K.; Ponimasov, O.E.; Titarenko, Yu.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of the reaction of the respiratory system of hockey players to a special physical load. Methods and structure of the study. The survey involved 25 qualified hockey players of various types of energy metabolism at the age of 16-18 years. On the basis of indicators of the response of the respiratory system of athletes to loads of varying intensity, additional reserves for increasing fitness were studied. Results and conclusions. The gradation of the reactivity of the respiratory system of hockey players, depending on the parametric algorithmization of the load, makes it possible to stimulate the deployment of additional reserves to increase fitness. Variation of non-specific load parameters is expedient in order to activate recovery based on a combination of aerobic and anaerobic mechanisms of energy metabolism of qualified hockey players.